Impacts of corporate governance mechanisms on dynamics of banks financial performance: empirical evidences from private commercial banks of Ethiopia - Ferede Mengistie Alemu; Misganaw Debas Worku (Cogent Business & Management)
This study aims to investigate the effects of corporate governance structures on the financial performance of private commercial banks in Ethiopia. For this purpose, panel data from 2014 to 2023 with the dynamic GMM estimation approach were used. From 2014 to 2023, the average board size for banks was 2.303, with an average gender composition of 22%. Moreover, the average bank size in Ethiopia has increased by 22.47% since 2018, while political uncertainty has had a two-way impact on private commercial banks in Ethiopia. The empirical results reveal that corporate governance (larger board size and gender composition), along with growth of bank size, capitalization ratio, and reserve ratio, has improved the financial performance of private commercial banks in Ethiopia by developing a solid structure for enhancing equity returns and integrating comprehensive strategies. However, political instability and a higher leverage ratio have freighted banks performances’. Therefore, private commercial banks enhance a suitable amount of bank size and board size to foster economic diversification, innovations, and managerial capability at the lowest operating cost; boost their reserve ratio and capitalization ratio to address the liquidity problem; and develop an integrated risk management strategy and leverage estimation to address uncertainties.